2012
DOI: 10.6061/clinics/2012(01)05
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis-associated risk factors in pregnant women

Abstract: OBJECTIVE:The main objective of this study was to investigate the risk factors associated with periodontitis in pregnant women.METHODS:This study was conducted in two stages. In Stage 1, a cross-sectional study was conducted to determine the prevalence of periodontitis among 810 women treated at the maternity ward of a university hospital. In Stage 2, the factors associated with periodontitis were investigated in two groups of pregnant women: 90 with periodontitis and 720 without. A hierarchized approach to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 29 publications
3
70
2
9
Order By: Relevance
“…Results were in the direction of overweight/obese women being more likely to have periodontal disease, although results were not precise enough to draw firm conclusions. This might be due to the high homogeneity of the study population - most of participants were not overweight, had a college or higher education, were employed, and were above the low income threshold – or it might indicate that the disparities seen in above studies that were mainly conducted in the United States and Brazil [9, 30, 31] are not apparent in our study population.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Results were in the direction of overweight/obese women being more likely to have periodontal disease, although results were not precise enough to draw firm conclusions. This might be due to the high homogeneity of the study population - most of participants were not overweight, had a college or higher education, were employed, and were above the low income threshold – or it might indicate that the disparities seen in above studies that were mainly conducted in the United States and Brazil [9, 30, 31] are not apparent in our study population.…”
Section: Discussionmentioning
confidence: 91%
“…Additional risk factors for periodontal disease include older age, Hispanic and non-Hispanic Black ethnicity, being overweight and obese, poor oral hygiene, more stressful psychological status, tobacco use, alcohol consumption, taking oral contraceptives, increased parity, gestational age, public dental insurance (versus private), and lacking a recent dental visit (within six months) [7, 9, 30, 31]. Although we have examined these potential associated factors in the analysis, the findings did not show socioeconomic status or other factors, except self-reported bleeding during tooth brushing, to be significantly associated with periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported a positive association between excessive weight and periodontitis during pregnancy. Nonetheless, these studies used different methodologies for the classification of periodontitis and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…[88] A cross-sectional study applied to evaluate factors associated with periodontitis, they found that the odds of having periodontitis in pregnant women who were overweight/obese before pregnancy was 2.22 times the odds in pregnant women with normal weight. [89] The risk of Periodontitis increases by l6% per increase of 1 kg/m 2 in ƁΜӀ. [90] Another study reporting a 57% risk of periodontitis per increase of 1 kg/m 2 in ƁΜӀ.…”
Section: Discussionmentioning
confidence: 99%
“…[104] Piscoya et al2012, who found that the prevalence of periodontitis was 11%. [89] Concerning with prevalence of periodontal disease in relation to prenatal weight among different gestational stages in the first, second and third trimester. The results of the present study revealed that, two-thirds (66.7%) of the studied women, who had prenatal obesity, complained from periodontal disease were in their first trimester, while more than half of them (51.4%) suffered in their second trimester and 53.2% complained in the third trimester.…”
Section: Discussionmentioning
confidence: 99%